Gross brain morphology of the armoured catfish Rineloricaria heteroptera, Isbrücker and Nijssen (1976), (Siluriformes: Loricariidae: Loricariinae): A descriptive and quantitative approach - Angulo, Arturo [UNESP]; Langeani, Francisco [UNESP] (Wiley, 2017)
The gross morphology of the brain of Rineloricaria heteroptera and its relation to the sensory/behavioural ecology of the species is described and discussed. The sexual and ontogenetic intraspecific variation in the whole brain length and mass, as well as within/between the eight different brain subdivisions volumes, is also examined and discussed. Negative allometry for the whole brain length/mass and relative growth of the telencephalon and optic tecta was observed. Positive allometry was observed for the relative growth of the olfactory bulbs and medulla oblongata. Univariate and multivariate statistical analyses did not reveal significant differences in the brain subdivision growth rates among sexes and/or developmental stages, except for the optic tectum and some portions of the medulla oblongata, with juveniles and males showing more developed optic tecta and medullary subdivisions, respectively. The growth rates for each brain subdivision were relatively constant, and the slopes of the growth equations were almost parallel, except for those of the olfactory bulbs and medulla oblongata subdivisions, suggesting some degree of tachyauxesis of subdivisions against the entire brain. The corpus cerebelli was the more voluminous brain subdivision in most specimens (principally adults), followed by the optic tectum (the more voluminous subdivision in juveniles), hypothalamus, and telencephalon, in that order. Differences in the number of lamellae and relative size of the olfactory organ were also detected among developmental stages, which were more numerous and larger in adults. Based on these results, it is possible to infer an ontogenetic shift in the habitat/resource use and behaviour of R. heteroptera. Vision, primarily routed through the optic tectum, could be fundamental in early stages, whereas in adults, olfaction and taste, primarily routed through the olfactory bulbs and medulla oblongata, play more important roles.
Keywords: brain organization; neotropical fish; ontogeny; sexual dimorphism; teleost